Lanthanide Fluorobenzoates as Bio‐Probes: a Quest for the Optimal Ligand Fluorination Degree. Issue 59 (22nd September 2017) - Kalyakina, Alena S.; Utochnikova, Valentina V.; Bushmarinov, Ivan S.; Le‐Deygen, Irina M.; Volz, Daniel; Weis, Patrick; Schepers, Ute; Kuzmina, Natalia P.; Bräse, Stefan
Abstract: The thorough study of fluorinated benzoates of lanthanides (Eu, Tb, Nd, Er, Yb, Gd, La, Lu) is reported. Their composition in single crystal and powder state revealed two predominant structural motifs. An in‐depth luminescence study has been performed on the reported fluorobenzoates, showing, that terbium and europium complexes in solid state possess high luminescence intensity with the quantum yield of up to 69 %. High solubility in most organic solvents, as well as in water, combined with the high luminescence intensity in water solution and non‐toxicity allowed the testing of europium complexes as bioprobes in cellulo. Among all tested fluorobenzoates, europium 2‐fluorobenzoate dihydrate combined the best luminescent properties, thermodynamic stability, aqueous solubility, and non‐toxicity, and was shown to be a viable bio‐marker. Abstract : Probe : An in‐depth study on the luminescence of fluorinated benzoates of lanthanides was performed, optimizing the fluorination degree of the complexes. This leads to a europium 2‐fluorobenzoate dehydrate showing excellent properties, as a viable bio‐marker.